The Dynamic and Distributional Aspects of Import Tariffs - Wolfgang Lechthaler; Mariya Mileva (International Economic Review, 2021)
We use a dynamic trade model with two sectors and two types of workers to analyze the optimal setting of income-generating tariffs. We study dynamic and distributional aspects focusing on the time horizon of policymakers and workers. The level of tariffs preferred by workers depends on the sector where they are employed as well as their skill class, with the relative weight of both aspects determined by the time horizon of the workers. Unskilled workers in the unskilled-intensive sector are the ones most in favor of protectionism and might even benefit from a trade war.
Keywords: 330